2003
DOI: 10.1016/s0014-5793(03)00044-9
|View full text |Cite
|
Sign up to set email alerts
|

The hypolipidemic drug metabolites nafenopin‐CoA and ciprofibroyl‐CoA are competitive P2Y1 receptor antagonists

Abstract: Coenzyme A (CoA-SH), endogenous and drug-derived CoA-derivatives were tested as putative antagonists of P2Y receptors expressed in Xenopus laevis oocytes, a method used to determine calcium-activated chloride current, an indicator of the activation of these receptors. CoA-SH antagonized reversibly and in a concentration-dependent manner the ATPgated currents evoked by the human P2Y 1 but not the P2Y 2 receptor. Palmitoyl-CoA was four-fold more potent than CoA-SH as an antagonist while palmitoyl-carnitine was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…A dipeptide conjugate of adenosine 49a was found to antagonize hP2Y 1 receptor responses with a K B value of 4.0 μM [49]. Metabolites of hypolipidemic drugs, such as the coenzyme A conjugate of nafenopin 49b, were found to act as P2Y 1 receptor antagonists [55]. 49b displayed a K B value of 58 nM at the human P2Y 1 receptor.…”
Section: Antagonistsmentioning
confidence: 99%
“…A dipeptide conjugate of adenosine 49a was found to antagonize hP2Y 1 receptor responses with a K B value of 4.0 μM [49]. Metabolites of hypolipidemic drugs, such as the coenzyme A conjugate of nafenopin 49b, were found to act as P2Y 1 receptor antagonists [55]. 49b displayed a K B value of 58 nM at the human P2Y 1 receptor.…”
Section: Antagonistsmentioning
confidence: 99%
“…PaCoA produced concentration–dependent inhibition of ADP‐evoked relaxation of the rat thoracic aorta, and its effects were reversible, as described at recombinant P2Y 1 receptors in Xenopus oocytes (Coddou et al ., ). PaCoA had no direct effect on the rat thoracic aorta, and was more potent than CoA and acetyl CoA as an antagonist at P2Y 1 receptors; indeed, 10 μM PaCoA caused an approximately 330‐shift of ADP‐evoked relaxations, while acetyl CoA at the same concentration produced a fivefold shift and CoA was ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a handful of papers have been published to date on extracellular signalling by CoA/acyl-CoA implicated mainly in the regulation of platelet aggregation and vasoconstriction [20][21][22][23].…”
Section: Extracellular Functions Of Coa/coa Thioestersmentioning
confidence: 99%
“…A few years later, Coddou et al [22] investigated the effect of hypolipidemic drug metabolites of CoA (nafenopin-CoA and ciprofibroyl-CoA) on the function of P2Y 1 receptors expressed in Xenopus laevis oocytes. In the course of their study, they found that nafenopin-CoA and ciprofibroylCoA, as well as palmitoyl-CoA, effectively antagonized the effect of ATP on Cl − currents mediated by P2Y 1 receptors in oocytes.…”
Section: Regulation Of Platelet Aggregation By Coa and Its Thioestersmentioning
confidence: 99%